Prinsip Restorative Justice Dengan Keseimbangan Orientasi Pada Penyelesaian Tindak Pidana - Umar Dinata; Aksar; Saut Maruli Tua Manik (UIR Law Review, 2022)
Settlement of criminal cases with a restorative approach has begun to be applied in Indonesia, but its implementation is only related to the settlement of juvenile criminal cases. In practice, a restorative justice approach is often applied to pay more attention to the perpetrators of crimes than to the victims of these crimes. Thus the reconstruction of the principles of restorative justice is currently not fully implemented. Investigators pay more attention to the interests of the perpetrator rather than the interests of the victim. Often victims feel dissatisfied or feel compelled to accept the decision. This was done by involving community leaders and traditional leaders, but the implementation still impressed the perpetrators and impressed that in the process the victims were forced to agree to the agreements that were made. The principle of restorative justice is known as a traditional case settlement model. The case settlement model with a restorative justice principle approach which is designed to resolve criminal cases in the context of modern criminal law, should be processed within the criminal justice system. Indonesia, and the Ministry of Law and Human Rights of the Republic of Indonesia have adopted the principle of restorative justice as a way of settling a criminal case so that conceptually it can produce provisions based on restorative justice.